USAHA PONDOK PESANTREN RIYADLUL JANNAH PACET MOJOKERTO DALAM MENGEMBANGKAN PEREKONOMIAN PESANTREN PERSPEKTIF ILMU EKONOMI SYARIAH - M Zidny Nafi’ Hasbi (LP2M Universitas Ibrahimy, 2021)
Investment is funds or resources to obtain future profits. Investment does not have to be in the form of money, sometimes land, agricultural land, thoughts that can build a business, etc. Restaurants, farms, fisheries, villas, wedding organizations are some of the business investments owned by Pondok Pesantren Riyadlul Jannah. This paper aims to find out how the implementation of business investment in Pondok Pesantren Riyadlul Jannah, what are the hardships faced by the company Pondok Pesantren Riyadlul Jannah, and how to overcome these hardships in developing the economy of Pondok Pesantren Riyadlul Jannah. It used qualitative methods which include data sources, data collection techniques, and data analysis techniques.